Theoretical and Experimental Approach on the Molecular Interactions of the Dl-Alanine with an Electrolytic Environment - Lopez-Polo, J (Elsevier B.V., 2017)
The molecular interactions that promote the stability of proteins and amino acids in saline solutions is a central topic of molecular biophysics. However, a well-supported molecular picture of the phenomena has not been established yet. In this paper, we studied as model system the mix between DL-Alanine in aqueous solutions of STP (Na2S2O3·5H2O) at different temperatures, from volumetric and viscometric properties. The thermophysical properties obtained indicate the presence of a strong preferential solvation, structure-making action and a possible salt in effect. Quantum chemical calculations and molecular dynamic (MD) simulations provide a new insight to support these arguments. © 2017 Elsevier B.V.